Chromosomal differentiation of schistosomes: what is the message? - Hirai, Hirohisa (Frontiers in Genetics, 2014)
As the only group of flukes with dioecism, schistosomes are unique organisms; they not only have intriguing biological and evolutionary aspects but also are responsible for major public health problems in the developing world. Schistosomiasis caused by this fluke affects approximately 210 million people in 76 countries. In order to facilitate the discovery of eradication methods for this disease, fundamental biological outcomes must be made available. Whole genome sequence data represent one such resource applicable to discovering eradication methods and measures. Herein, I describe three remarkable chromosomal changes and briefly discuss the differentiation of the Asian and African groups of this parasite taxon. Chromosomal data and evolutionary aspects will enable us to exploit genomic information for advancing schistosome studies.